2015
DOI: 10.2495/sdp150611
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable community initiatives: a unique partnership and participatory approach

Abstract: Existing research on partnerships between local governments and communitybased organizations within Local Agenda 21 processes across the globe have embarked primarily on the advantages of partnership within the philosophical discourse of community participation as well as the barriers of such participation and their effects on intended partnership. Both empirical and qualitative findings which mostly cover the cases from the United Kingdom and European countries revealed the need to explore more in-depth aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Petaling Jaya had an opportunity to engage in the pursuit of sustainable development when its city council became among the four selected local authorities out of 145 local authorities nationwide to implement the first round of Local Agenda 21 in Malaysia (Mokhtar & M.Dali, 2015). In 2003, the Ministry of Housing and Local Government (MHLG) published LA21 Guide and Case Studies which acknowledged the best practices of partnership and participation by the City Council of Petaling Jaya or Majlis Bandaraya Petaling Jaya (MBPJ) in LA21 to serve as guidelines for other local authorities.…”
Section: Local Agenda 21 In Petaling Jayamentioning
confidence: 99%
See 1 more Smart Citation
“…Petaling Jaya had an opportunity to engage in the pursuit of sustainable development when its city council became among the four selected local authorities out of 145 local authorities nationwide to implement the first round of Local Agenda 21 in Malaysia (Mokhtar & M.Dali, 2015). In 2003, the Ministry of Housing and Local Government (MHLG) published LA21 Guide and Case Studies which acknowledged the best practices of partnership and participation by the City Council of Petaling Jaya or Majlis Bandaraya Petaling Jaya (MBPJ) in LA21 to serve as guidelines for other local authorities.…”
Section: Local Agenda 21 In Petaling Jayamentioning
confidence: 99%
“…A preliminary study has shown that the implementation of LA21 in Petaling Jaya within the span of fifteen years has generated learning communities under strong and charismatic leaderships (Mokhtar & M.Dali, 2015). While such research explores some relationship between community participation, leadership, and learning, a deeper investigation into their relationship with liveability may contribute better to the understanding of CBOs' roles in partnership and participation arrangements.…”
Section: Introductionmentioning
confidence: 99%